Materials for design 2 - Ballard Bell, Victoria, ....-; Rand, Patrick, 1950- (New York : Princeton Architectural Press, 2014)
As architecture and design programs throughout the world break out of the classroom and adopt the holistic methods of design/build programs, the need for a textbook that bridges the gap between construction materials and design sensibility is sorely needed. In Materials for Design 2, authors Victoria Ballard Bell and Patrick Rand revisit the format of their award-winning first volume and present sixty new case studies of materials put to imaginative use by today's brightest architects. Bell and Rand introduce each material type—glass, concrete, wood, metal, plastic, and stone—with new text describing its history and significance. Accessible case studies highlight recent advances in design and construction around the world—from a wooden church in Finland and huts in Thailand to a bank encased in a glass cube in Denmark. In a materials landscape that constantly changes to meet the demands of contemporary designers, Materials for Design 2 is an up-to-date guide to the best and most exciting materials at their disposal.
Keywords: Building materials; Architectural design; Architecture, modern -- 21st century; Architecture / methods & materials